Implementation of PJBL to Instill Values of Tolerance and Cultural Diversity in Elementary School Students - Astuti, Widya Sri; Wibawa, Sutrisna (Universitas of Muhammadiyah Makassar, 2025)
This research examines the application of Project Based Learning (PJBL) in Citizenship Education subjects to instill the values of tolerance and cultural diversity in fifth grade elementary school students. Using a qualitative descriptive approach, data was collected through observation, interviews and documentation, and analyzed using qualitative coding techniques using NVivo software and triangulation to ensure data validity. Measurement of increased awareness of tolerance was carried out by comparing pre and post intervention scores, which showed that the initial average score of 50 increased to 65 in cycle I and reached 85 in cycle II. Apart from that, students' creativity in producing learning products increased significantly, with an average score reaching 95 in cycle III. These findings reveal the real impact of PJBL in improving students' collaboration skills, creative expression and inclusive attitudes, thereby supporting the strengthening of educational character. The practical implications suggest broader integration of PJBL in the basic education curriculum in Indonesia as an effective strategy to foster civic values from an early age. This article contributes to the development of the character of PJBL-based education by providing empirical evidence of the effectiveness of this method in fostering cultural tolerance and diversity.